Development and validation of an HPLC–MS/MS method for the analysis of dexamethasone from pig synovial fluid using dried matrix spotting. (November 2010) - Christianson, Chad D; Laine, Derek F; Zimmer, Jennifer SD; Johnson, Casey JL; Sheaff, Chrystal N; Carpenter, Anna; Needham, Shane R
Background: Dried matrix spot techniques were employed to validate an HPLC–MS/MS assay for the determination of dexamethasone in clear Yorkshire pig synovial fluid using 15 µl of sample. We have adopted the term dried matrix spot to indicate that the techniques used for dried blood spots can be applied to nonblood matrices. The dried matrix spot method employs a color-indicating process developed at Alturas Analytics that enhances the ability to analyze transparent fluids spotted onto collection paper by allowing the analyst to visually verify the location of the dried sample spot.Results: The method was shown to be accurate (±4.3%) and precise (14.2% at the LLOQ and ≤10.0% at all other concentrations) across the dynamic range of the assay.Conclusion: The method shows the potential application of dried matrix spot techniques for the analysis of transparent biological fluids.